Satisfaction and associated factors in students who use the dental services of the health care institution “IPS Universitaria” (Medellín) - Agudelo-S., Andrés Alonso; Valencia-L., Luz Yanneth; Oullón-H., Eliana; Betancur-G., Luis Guillermo; Peláez-D., Laura Victoria; Restrepo, Lina Marcela (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: dental Health Care Services incorporate patient satisfaction evaluation as a component of quality. The purpose of this study was to evaluate students’ satisfaction with the dental services provided by the "Institución Prestadora de Servicios de Salud IPS" of the University of Antioquia from the perspective of the patient and the professional who provides the service. Methods: a descriptive study was carried out in 98 students by means of qualitative and quantitative techniques such as survey on aspects like as personnel behavior, efficacy in the service rendered, information, accessibility, opportunity, safety, opinion on the facilities, overall satisfaction; it was complemented with a semi structured interview with the dentists and the students. Results: a high overall satisfaction (95.9%) was found along with elements that emphasize the technical and professional confidence of the dental personnel and the institution itself (averages above 7 for the variables studied, and percentages of high satisfaction above 50%); with some critical elements in the service that must be improved such as privacy, and opportune service. Conclusions: patient satisfaction is high in comparison with other local studies, and it depends on factors such as gender, age, social economic status, the institution, and the patient-professional relationship. This study suggests new research proposals in the patient satisfaction area in other institutions, and also proposes degrees of patient satisfaction in the dental services in order to obtain validation so they can be used in other institutions.